Binary N, S-doped carbon nanospheres from bio-inspired artificial melanosomes: A route to efficient air electrodes for seawater batteries. Issue 47 (21st November 2018) - Khan, Ziyauddin; Park, Sung O; Yang, Juchan; Park, Seungyoung; Shanker, Ravi; Song, Hyun-Kon; Kim, Youngsik; Kwak, Sang Kyu; Ko, Hyunhyub
Abstract : N, S-doped carbon nanoshpers (NSCSs) were prepared by bio-inspired artificial melanin and were explored as air electrode in seawater-electrolyte based cells under flow off and on both mode. Abstract : Cost-effective and environmentally friendly seawater-electrolyte-based batteries exhibit high energy density and demonstrate immense potential for use in future energy storage devices; however, lack of high-performance negative and positive electrodes significantly challenges their practical applications. In this study, N-doped and N, S-doped carbon nanospheres (referred to as NCSs and NSCSs, respectively) are synthesized via the pyrolysis of melanosomes, which is a bio-inspired polymer. Electrocatalytic activity measurements reveal the bifunctionality of the prepared catalysts. NSCSs exhibit a distinctively higher performance than NCSs when used as an air electrode in seawater batteries under ambient conditions (referred to as static mode hereafter). Further, due to the introduction of air flow into the seawater electrolyte (referred to as flow mode hereafter), NSCSs exhibit an improved cell discharge potential. The high performance of the cell is attributed to the high surface area, bifunctional electrocatalytic activity, generation of new active sites, improvement of spin density in NSCSs, and continuous flow of air to the electrolyte. The cell in the flow mode exhibits an overpotential gap of 0.56 V, a round-trip efficiency of 84%, a maximum power density of 203 mW g −1, and an outstanding cycling stability up to 100 cycles. The developed synthetic method provides an effective, scalable approach for doping binary or ternary atoms into the carbon host matrix, which can motivate further experimental and theoretical studies of electrode materials in various energy storage devices. In addition, the concept and results obtained by the introduction of air flow into the electrolyte can lead to the improvement of cell performance in terms of electrical energy efficiency, which can be exploited in various metal–air batteries.